2014
DOI: 10.1111/1751-7915.12107
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies on a versatile esterase that is most catalytically active with polyaromatic esters

Abstract: Herein, we applied a community genomic approach using a naphthalene-enriched community (CN1) to isolate a versatile esterase (CN1E1) from the α/β-hydrolase family. The protein shares low-to-medium identity (≤ 57%) with known esterase/lipase-like proteins. The enzyme is most active at 25–30°C and pH 8.5; it retains approximately 55% of its activity at 4°C and less than 8% at ≥ 55°C, which indicates that it is a cold-adapted enzyme. CN1E1 has a distinct substrate preference compared with other α/β-hydrolases bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…6A), which was generated from a binomial distribution based on the presence or absence of activity at 30°C and at pH 8.0 against the set of 131 different esters used in this study and reported previously (3,6,27,28,37,53), revealed that the three characterized carboxyl esterases clustered separately, consistent with the finding that they possess different substrate spectra (Fig. 4 and 5).…”
Section: Figsupporting
confidence: 86%
See 1 more Smart Citation
“…6A), which was generated from a binomial distribution based on the presence or absence of activity at 30°C and at pH 8.0 against the set of 131 different esters used in this study and reported previously (3,6,27,28,37,53), revealed that the three characterized carboxyl esterases clustered separately, consistent with the finding that they possess different substrate spectra (Fig. 4 and 5).…”
Section: Figsupporting
confidence: 86%
“…These chemicals included 11 model esters (7 pNP esters and 4 triacylglycerols) (Fig. 4), as well as a battery of 120 structurally different esters (3,6,27,28,37,53) (Fig. 5).…”
Section: Metagenome Library Construction and Screening For Carboxyl Ementioning
confidence: 99%
“…This result implies that the enzymes with the lipase phenotype (most active against longer insoluble triglycerides such as triolein) were 83‐fold less abundant in this experiment than were those with an esterase (most active towards shorter triglycerides such as tributyrin) character. Additionally, among the common substrates used for the esterase/lipase screen, the methods using pH indicators resulted in a higher incidence rate (1:29) (Martínez‐Martínez et al ., ), followed, to a lesser extent, by methods based on the utilization of indoxyl acetate (1:700) (Alcaide et al ., ), nitrocefin [3‐(2, 4 dinitrostyrl)‐(6R,7R‐7‐(2‐thienylacetamido)‐ceph‐3‐em‐4‐carboxylic acid, E‐isomer)] (1:10 000) (Rashamuse et al ., ), poly(DL‐lactic acid) (1:13 334) (Akutsu‐Shigeno et al ., ; Okamura et al ., ), tributyrin (1:15 478), α‐naphthyl acetate (1:19 925), polyethylene terephthalate (1:21 400) (Sulaiman et al ., ), triolein/olive oil and rhodamine B (1:22 061) (Glogauer et al ., ), Tween‐20 and CaCl 2 (1:26 496) (Heravi et al ., ; Okamura et al ., ), methyl and ethyl ferulate (1:26 496) (Vieites et al ., ), 5‐bromo‐4‐chloro‐3‐indolylcaprylate (1:50 000) (Li et al ., ), and tricaprylin (1:68 279) (Tirawongsaroj et al ., ), in that order (Fig. A).…”
Section: Quantifying the Success Of The Screening Protocols For Enzymmentioning
confidence: 99%
“…Most of the LIP-EST enzymes can recognize the carboxyl group on fatty acids, alkanes and, in general terms, long chain structures where the carboxyl group is located at one end. However, the process does not work as well when the carboxyl group is near a bigger, more complex, and especially less flexible, structure, such as oleanolic acid, abietic acid, or generally speaking naphtene, phenantrene or terpenoid structures (Martínez-Martínez et al 2014). Another problem to be addressed is how to perform the reaction when the substrate/substrates (the acid and/or the alcohol molecules) are nearly insoluble in water or in solvents where the LIP-EST enzymes are active.…”
Section: Biocatalysis Innovation Guided By Metagenomicsmentioning
confidence: 99%